2015
DOI: 10.32473/edis-in1069-2014
|View full text |Cite
|
Sign up to set email alerts
|

Wedge-Shaped Beetles (suggested common name) Ripiphorus spp. (Insecta: Coleoptera: Ripiphoridae)

Abstract: Ripiphoridae are a family of unusual parasitic beetles that are thought to be related to tumbling flower beetles and blister beetles. They parasitize bees and wasps, roaches, and wood-boring beetles, but specific hosts for many ripiphorid species are unknown. Their secretive life cycle makes an assessment of their economic and ecological impact very difficult. Additional research is necessary to determine the abundance and impact of Ripiphorus species. This 4-page fact sheet was written by David Owens, Ashley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We found several Crabronidae, Sphecidae, and Vespidae wasps nesting in our nests sites (Graham 2014), making them a possible host for M. cruenta in this study. Ripiphorus fasciatus have been recorded parasitizing Apidae and Halictidae (Owens et al 2015), including Lasioglossum pruinosum (Robertson) and L. zephyrum (Smith) (Hymenoptera: Halictidae) (Batelka and Straka 2011). While Lasioglossum were present at many of the field sites during this study, none were observed nesting in the provided artificial nest materials (Graham 2014), and Lasioglossum are generally regarded as ground-nesting bees.…”
Section: Coleoptera -Ripiphoridaementioning
confidence: 73%
See 1 more Smart Citation
“…We found several Crabronidae, Sphecidae, and Vespidae wasps nesting in our nests sites (Graham 2014), making them a possible host for M. cruenta in this study. Ripiphorus fasciatus have been recorded parasitizing Apidae and Halictidae (Owens et al 2015), including Lasioglossum pruinosum (Robertson) and L. zephyrum (Smith) (Hymenoptera: Halictidae) (Batelka and Straka 2011). While Lasioglossum were present at many of the field sites during this study, none were observed nesting in the provided artificial nest materials (Graham 2014), and Lasioglossum are generally regarded as ground-nesting bees.…”
Section: Coleoptera -Ripiphoridaementioning
confidence: 73%
“…Macrosaigon cruenta (Germar) and Ripiphorus fasciatus Say are beetles in the family Ripiphoridae whose natural histories were described by Linsley et al (1952) and Majka et al (2006). Macrosaigon cruenta has been reported to parasitize numerous bee (Apidae, Halictidae) and wasp families (Crabronidae, Pompilidae, Sphecidae, Tiphiidae, Vespidae) (Owens et al 2015). We found several Crabronidae, Sphecidae, and Vespidae wasps nesting in our nests sites (Graham 2014), making them a possible host for M. cruenta in this study.…”
Section: Coleoptera -Ripiphoridaementioning
confidence: 99%
“…On the other hand, species of Ripiphorus (Fig. 5) are parasitoids of solitary and subsocial bees from Apidae and Halictidae (Owens et al 2015). Within Halictidae, several genera are used as hosts, including Halictus Latreille, 1804 and Lasioglossum Curtis, 1833, also very diverse taxa within the Iberian Peninsula (Ortiz-Sánchez 2011, Owens et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…5) are parasitoids of solitary and subsocial bees from Apidae and Halictidae (Owens et al 2015). Within Halictidae, several genera are used as hosts, including Halictus Latreille, 1804 and Lasioglossum Curtis, 1833, also very diverse taxa within the Iberian Peninsula (Ortiz-Sánchez 2011, Owens et al 2015). In both cases (M. bimaculata and R. subdipterus), as well as for the rest of the species of Ripiphoridae, it is essential that the dispersal areas are not only those that present suitable environmental conditions for the adults, but also those where potential hosts for larval development are present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation